2005
DOI: 10.1103/physrevb.72.035329
|View full text |Cite
|
Sign up to set email alerts
|

General topological features and instanton vacuum in quantum Hall and spin liquids

Abstract: We introduce the concept of super universality in quantum Hall liquids and spin liquids. This concept has emerged from previous studies of the quantum Hall effect and states that all the fundamental features of the quantum Hall effect are generically displayed as general topological features of the θ parameter in nonlinear σ models in two dimensions.To establish super universality in spin liquids we revisit the mapping by Haldane who argued that the anti ferromagnetic Heisenberg spin s chain in 1 + 1 space-tim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 17 publications
(10 reference statements)
0
32
0
Order By: Relevance
“…non-linear sigma model in two dimensions it was shown that the ϑ vacuum generally displays massless excitations that propagate along the confining "edge" of the system [1][2][3][4][5]. This new aspect of the sigma model has come in many ways as a welcome surprise.…”
Section: Super Universality In a Series Of Investigations On The Grasmentioning
confidence: 99%
See 3 more Smart Citations
“…non-linear sigma model in two dimensions it was shown that the ϑ vacuum generally displays massless excitations that propagate along the confining "edge" of the system [1][2][3][4][5]. This new aspect of the sigma model has come in many ways as a welcome surprise.…”
Section: Super Universality In a Series Of Investigations On The Grasmentioning
confidence: 99%
“…In applications to quantum A.M.M. Pruisken ( ) Institute for Theoretical Physics, University of Amsterdam, Valckenierstraat 65, 1018 XE Amsterdam, The Netherlands e-mail: pruisken@science.uva.nl spin liquids [6,7], for example, the edge excitations describe the dynamics of the "dangling" quantum spins located at the "edges" of the spin chain [4,5]. In the context of quantum Hall liquids [8][9][10][11][12], on the other hand, these excitations are identically the same as those described by the theory of "chiral edge bosons" [2,3].…”
Section: Super Universality In a Series Of Investigations On The Grasmentioning
confidence: 99%
See 2 more Smart Citations
“…Haldane's analysis used a non-linear σ-model (NLSM) which is a field theoretic description of the long-distance and low-energy modes of the spin system [3,4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%